Edukasi Bahaya dan Upaya Pencegahan Rokok Remaja di SMA Negeri 1 Seram Bagian Barat - Dusra, Ety; Epi Dusra; Suryanti Tukiman (FKIP, Universitas Palangka Raya, 2025)
Smoking remains a major public health issue that is difficult to address, particularly among adolescents. The rising number of young smokers is a concerning issue due to the long-term detrimental consequences it poses, both in terms of health, social, and economic aspects. Adolescence is a period of identity exploration and challenges, and unfortunately, many young people fall into the habit of smoking. The community service conducted at SMA Negeri 1 Seram Bagian Barat on october 17, 2024, aimed to raise awareness about the dangers of smoking and prevention efforts. The activity involved socialization, interactive discussions, and pre-test and post-test assessments to measure participants' knowledge changes. The results showed an increase in students' knowledge about the dangers of smoking. Additionally, interviews with participants revealed that peer influence and family environment played a significant role in influencing adolescent smoking behavior. These findings support Bandura's Social Learning Theory, which states that behavior is largely influenced by observation of one's social environment. Efforts to prevent smoking among adolescents need to involve active participation from families, schools, and communities.